2020
DOI: 10.1007/s00299-020-02567-3
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplasts in C3 grasses move in response to blue-light

Abstract: Key message Brachypodium distachyonis a good model for studying chloropla st movements in the crop plants, wheat, rye and barley. The movements are activated only by blue light, similar to Arabidopsis. Abstract Chloroplast translocations are ubiquitous in photosynthetic organisms. On the one hand, they serve to optimize energy capture under limiting light, on the other hand, they minimize potential photodamage to the photosynthetic apparatus in excess light. In higher plants chloroplast movements are mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Often a mixture of red and blue light with a high red to blue light ratio increases the chlorophyll contents in the leaves of the plant due to the activation of the formation of chloroplasts. Krzeszowiec and co-workers [ 44 ] reported that powerful blue light caused chloroplasts to aggregate at cell walls parallel to the light path (avoidance response), while weak blue light caused them to relocate to the most illuminated cell walls (accumulation response).…”
Section: Discussionmentioning
confidence: 99%
“…Often a mixture of red and blue light with a high red to blue light ratio increases the chlorophyll contents in the leaves of the plant due to the activation of the formation of chloroplasts. Krzeszowiec and co-workers [ 44 ] reported that powerful blue light caused chloroplasts to aggregate at cell walls parallel to the light path (avoidance response), while weak blue light caused them to relocate to the most illuminated cell walls (accumulation response).…”
Section: Discussionmentioning
confidence: 99%
“…As an indispensable environmental factor, light is involved in many biological processes, including plant growth and development, photomorphogenesis, chlorophyll biosynthesis, and chloroplast development [ 1 , 2 ]. In order to ensure their normal growth and development, higher plants have evolved sophisticated and multiple photoreceptors which can sense and adapt to the light environment, such as phytochromes, cryptochromes, phototropins, and ultraviolet-B (UV-B) receptors [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phototropins play a key role in the chloroplast movement [ 5 ]. A recent study indicated that blue light induces chloroplast movement in several monocot plants such as Brachypodium , rye, wheat and barley [ 6 ], and Phalaenopsis aphrodite [ 7 ]. If excess light absorption cannot be avoided, the over-excitation of the light-harvesting complex pigments can be alleviated via the dissipation of excess light energy as heat via nonphotochemical quenching (NPQ) and manipulating the photosynthetic efficiency to enhance plant growth and significantly increase crop yield, as has been reported [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%